Design of water surface collection robot based on deep sea cage culture. Issue 1 (1st March 2022) - Liang, Yicha; Liu, Can; He, Taihua; Wang, Lin; Luo, Yingtong; Hou, Mingxin
Abstract: At present, the collection of floating garbage such as dead fish in deep and far sea cage culture waters mainly depends on manpower, which is not only difficult and inefficient, but also has great potential safety hazards. In order to solve the above problems, a water surface collection robot based on marine cage culture is designed and developed. The dead fish on the water surface are collected through the joint action of propeller and forearm drainage and retraction device. At the same time, the relevant performance indexes of the designed water surface collection robot are verified by making the prototype and water surface collection experiments, which meets the needs of simple and efficient collection and cleaning of dead fish in deep and open sea cage culture, so as to provide a reference basis for the practical application of the collection robot.